Natural deep eutectic solvent-assisted pectin extraction from pomelo peel using sonoreactor: experimental optimization approach - Elgharbawy, Amal A.M.; Hayyan, Adeeb; Hayyan, Maan; Mirghani, Mohamed Elwathig Saeed; Mohd. Salleh, Hamzah; Rashid, Shahidah Nusailah; Ngoh, Gek Cheng; Liew, Shan Qin; Mohd Nor, Mohd Roslan; Zulkifli, Mohd Zamani; Alias, Yatimah (MDPI, 2019)
Background: Natural deep eutectic solvents (NADESs) can be used for extracting a wide range of biomaterials, such as pectin. This study introduces a new generation of natural solvents for pectin extraction which could replace the conventional solvents in the food industry. Methods: In this study, NADESs were used for pectin extraction from pomelo (Citrus grandis (L.) Osbeck) peels using a sonoreactor. Definitive screening design (DSD) was used to screen the influence of time, temperature, solid/liquid ratio, and NADES/water ratio on the pectin yield and degree of esterification (DE). Results: The primary screening revealed that the best choices for the extraction were choline chloride–malonic acid (ChCl-Mal) and choline chloride–glucose–water (ChCl:Glc:W). Both co-solvents yielded 94% pectin and 52% DE after optimization at 80 ◦C, with 60 min of sonication, pH < 3.0, and a NADES-to-water ratio of 1:4.5 (v/v). Morphological screening showed a smooth and compact surface of the pectin from ChCl-Mal where glucose-based pectin had a rough surface and lower DE. Conclusions: NADESs proved to be promising co-solvents for pectin extraction with a high degree of esterification (>55%).